Utilizing the All-terrain Capable Mars Rover as Robotic Platform for Field Application in Tech-based Smart Agriculture - Aula, Abqori; Syaifurrahman; Fitriah (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2024)
NASA’s explorer robot rovers were primarily famous for its capability of exploring the rough and unknown terrain of planet Mars. The main suspension system of the rover has been an attraction for robotic enthusiasts due to its simple yet effective design, the so-called rocker-bogie system. Since its launch, this suspension system has been further researched, explored, and developed for different purpose and area of application. This paper proposes the design and development of a robotic platform utilizing the mentioned capability of Mars rover to explore the uneven terrain of farming field usually found in local precincts. The proposed robot has 6, all-driven wheels. Using the six-wheeled driven robot platform, the proposed system is tasked to autonomously explore the farming field. It can be tasked for a variety of purposes, such as soil inspection, weather checking, general mapping, and sample extraction. A couple of prototypes are designed and built to evaluate the exploring capability, the sensor accommodation capacity, as well as the electrical and electronic required. Preliminary results show that the robot platform can perform well in roving uneven terrain and can accommodate a variety of sensors either placed inside its enclosure or placed on its robotic arm.